Diet of Leptodactylus macrosternum (Miranda-ribeiro 1926) (Anura: Leptodactylidae) in the Caatinga domain, Northeastern Brazil, Neotropical region - Teles, Diêgo Alves; Rodrigues, Jennifer Katia [UNESP]; Teixeira, Adonias Aphoena Martins; Araujo-Filho, João Antonio de; Sousa, José Guilherme Gonçalves; Ribeiro, Samuel Cardozo (My University, 2018)
We analysed the diet of Leptodactylus macrosternum from the municipality of Milagres, Ceará State, Northeastern Brazil, during September 2011. Coleoptera and Hymenoptera were the most frequent prey. Orthoptera was volumetrically most important. The most abundant items in the diet of L. macrosternum were insect eggs. The diet of L. macrosternum comprises a wide variety of items similar to prey consumed by other species of Leptodactylidae within the Neotropical region. The results suggest that L. macrosternum have a generalist feeding habit.
Keywords: Amphibia; Feeding habitats; Predation; Semi-arid region